Osteoarthritis and Neuromuscular Deficits: Can a Causative Role be Discounted- Key 2017-2022 Observations - Ray, Marks (Journal of Aging Research And Healthcare, 2022)
Background The origin of osteoarthritis, the most common disabling disorder of older adults remains uncertain. Aim This mini review examines the possible role played by various neuromuscular deficits in the osteoarthritis etiopathogenic process. Methods and Procedures Articles that haveaddressed the current topic of interest and were located in the PUBMED,Google Scholar, and Web of Science electronic data bases as of 2017-2022 were carefully sought and examined. Results Various neuromuscular mechanisms may have a bearing on the development and progression of osteoarthritis, but the data are largely unrelated and observational in nature. Conclusion More research to examine this issue is sorely needed and could have considerable merit in light of the growing populations of older adults at risk for disabling osteoarthritis in the face of few intervention options to help them to achieve an optimal functional level.
Keywords: Aging; Muscles; Neuromuscular Deficits; Osteoarthritis; Prevention; Outcomes